Secondary Malignancies of the Bladder: Avoiding the Diagnostic Pitfall. (April 2018) - Feldman, Alexander; Borak, Samuel; Rais-Bahrami, Soroush; Gordetsky, Jennifer
Although rare, secondary tumors of the bladder can present a diagnostic dilemma to pathologists considering a differential diagnosis of primary bladder cancer. We investigated the clinicopathologic and imaging characteristics of metastatic tumors to the bladder. We retrospectively reviewed the surgical pathology databases from 2 sites from 2013 to 2016, identifying 66 cases of secondary bladder tumors. Clinical, pathologic, and imaging findings were reviewed. Mean age at diagnosis was 63 years (range = 25-87). Females had a significantly higher proportion (44/66, 66.7%) of secondary bladder tumors compared with males (22/66, 33.3%; P = .007). In total, 56/66 (84.8%) patients had a clinical history of an in situ or invasive malignancy in another organ, and 54/66 (81.8%) patients had imaging supporting a metastatic tumor. Only 2/66 (3.0%) patients had a prior history of urothelial carcinoma. In total, 4/66 (6.1%) cases (all females) were originally misdiagnosed as primary bladder malignancies and were corrected after clinicoradiologic correlation. Overall, colorectal origin was most common (15/66, 22.7%), followed by cervical and ovarian primaries (10/66, 15.2% each). Cervical and ovarian origins predominated in the female cohort (10/44, 22.7% each), followed by endometrial (8/44, 18.2%). Colorectal and prostate primaries were the most common among males (10/22, 45.5%, and 7/22, 31.8%, respectively). Secondary bladder tumors can mimic urothelial carcinomas. In our cohort, gynecological, colorectal, and prostatic origins were most common. Clinical history, imaging, and immunohistochemical studies can be useful in avoiding this diagnostic pitfall.